Problems in the Implementation of Restorative Justice at the Inquiry Stage under Law Number 20 of 2025 on the Criminal Procedure Code - Sofie Rahadatul Aisya; Deny Guntara; Muhamad Abas; Raka Indra Pratama (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
Law Number 20 of 2025 concerning the Criminal Procedure Code (KUHAP) introduces restorative justice as part of the reform of Indonesia’s criminal justice system. However, the implementation of restorative justice at the inquiry stage continues to raise legal concerns because the status of the alleged offender and the victim has not yet been definitively established, while the case may already be resolved through a reconciliation mechanism. This study aims to analyze the regulation of restorative justice under Articles 79 to 84 of the 2025 Criminal Procedure Code and to identify the challenges arising from its implementation during the inquiry stage. The research employs a normative legal method using statutory and conceptual approaches through qualitative analysis of primary and secondary legal materials. The findings indicate that the restorative justice provisions contained in the 2025 Criminal Procedure Code have accommodated victim-oriented recovery and dialogic dispute resolution. Nevertheless, their implementation at the inquiry stage still presents several challenges, including the unclear legal status of the parties involved, inadequate fact verification, limited supervisory mechanisms, and the potential abuse of authority that may weaken victim protection. Therefore, more comprehensive regulations concerning case eligibility standards, supervisory mechanisms, and victim protection are required to ensure that the implementation of restorative justice remains consistent with the objectives of criminal justice system reform.